The Main Task of the New Uzbekistan is to Increase the Legal Literacy and Culture of Young People - Jumaev Sarvarbek (International Journal on Human-Computing Studies, 2021)
this article describes more broadly the reforms in the education system and new theologies in the teaching of legal sciences, the results of the analysis.